MEMBANGUN KARAKTER SISWA MELALUI LITERASI DIGITAL DALAM MENGHADAPI PENDIDIKAN ABAD 21 - Pinasti Putri; Putri Harianti; Riliana Andriani; Arita Marini (Bajang Institute, 2022)
Abstract: Character education is a conscious and planned effort by humans to empower and guide students with the aim of shaping the character of students. Technological developments in the world of education create many conveniences such as increasing students' learning abilities and facilitating student access to learning. However, if its use is not balanced with the cultivation of character education, there will be a decline in character values. Therefore, the understanding and use of digital literacy need to be improved to shape the character values ​​of students in the 21st century. The purpose of this research is to find out the benefits of digital literacy in growing and building the character of students. This study uses a descriptive-qualitative method with a literature study approach and data sources obtained from the results of journal analysis. The results of the research analysis are that in shaping the character of students in the 21st century, digital literacy has an important role because students tend to be interested in things related to technology and social media that can be used by teachers as a forum to build student character values. The conclusion of the study is that in the use of digital literacy, teacher and parent supervision is needed by setting limits for students so that they can avoid the negative impacts caused. Keywords: Education, Digital Literacy, Character.